Recent progress and new developments in post-combustion carbon-capture technology with amine based solvents. (September 2015) - Liang, Zhiwu (Henry); Rongwong, Wichitpan; Liu, Helei; Fu, Kaiyun; Gao, Hongxia; Cao, Fan; Zhang, Rui; Sema, Teerawat; Henni, Amr; Sumon, Kazi; Nath, Devjyoti; Gelowitz, Don; et al.
Highlights: The recent progress and new developments of solvents used in the PCC systems were extensively reviewed and summarized. This paper covers the key issues, including solvent chemistry, process design, solvent management and post-built operations. The main challenge of this technology is still – how to further reduce the energy consumption. Abstract: Currently, post-combustion carbon capture (PCC) is the only industrial CO2 capture technology that is already demonstrated at full commercial scale in the TMC Mongstad in Norway (300, 000 tonnes per year CO2 captured) and BD3 SaskPower in Canada (1 million tonnes per year CO2 captured). This paper presents a comprehensive review of the most recent information available on all aspects of the PCC processes. It provides designers and operators of amine solvent-based CO2 capture plants with an in-depth understanding of the most up-to-date fundamental chemistry and physics of the CO2 absorption technologies using amine-based reactive solvents. Topics covered include chemical analysis, reaction kinetics, CO2 solubility, and innovative configurations of absorption and stripping columns as well as information on technology applications. The paper also covers in detail the post build operational issues of corrosion prevention and control, solvent management, solvent stability, solvent recycling and reclaiming, intelligent monitoring and plant control including process automation. In addition, the review discusses the most up-to-date insights related to the theoretical basis of plant operation in terms of thermodynamics, transport phenomena, chemical reaction kinetics/engineering, interfacial phenomena, and materials. The insights will assist engineers, scientists, and decision makers working in academia, industry and government, to gain a better appreciation of the post combustion carbon capture technology.